Ownership and efficiency in engineering firms in India, 1990-91 to 1999-2000 - B.N. Goldar; V.S. Renganathan; Rashmi Banga (Indian Council for Research on International Economic Relations (ICRIER), 2003)
The paper analyzes the effect of ownership on efficiency of engineering firms in India in the 1990s, a decade of major economic reforms. Technical efficiency of firms, estimated with help of a stochastic frontier production function, is considered for the analysis. A comparison of technical efficiency is made among three groups of firms in Indian engineering: (1) firms with foreign ownership, (2) domestically owned private sector firms, and (3) public sector firms. The results clearly indicate that foreign firms in Indian engineering industry have higher technical efficiency than domestically owned firms. No significant difference in technical efficiency is found between private sector and public sector firms among the domestically owned firms. There are indications of a process of efficiency convergence - the domestically owned firms tending to catch up with foreign owned firms in terms of technical efficiency. The results show a positive relationship between international trade orien
Keywords: 330